2022
DOI: 10.1111/odi.14261
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of injectable platelet‐rich fibrin in the treatment of symptomatic oral lichen planus

Abstract: Objectives: The use of autologous platelet concentrates has shown growing evidence as a promising therapy. We conducted a split-mouth study to evaluate the effectiveness of injectable platelet-rich fibrin (PRF) compared with triamcinolone acetonide (TA) in the treatment of oral lichen planus (OLP). Materials and methods:This split-mouth randomized trial included 12 patients with symptomatic, bilateral OLP lesions. The participants were randomly allocated to receive a 1-ml intralesional PRF injection on one sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“… Lesion Type of PCs Effect of PCs Ref. Oral lichen planus PRF membrane PRF resulted in a decrease in lesions' size within 3 weeks of treatment 36 Platelet solution PC improved quality of life and decreased pain 35 PRP Complete regression of the lesion after 4 weeks 41 PRP 90% of patients reported complete resolution of erythema 40 PRP Significant reduction in pain, size of the lesion and inflammation 37 i-PRF i-PRF reduced the lesion size by 59.8% and reduced the VAS scores by 47.6% 65 i-PRF i-PRF reduced pain and lesion's size 44 PRP PRP reduced pain and size of the ulcers 39 i-PRF i-PRF reduced VAS scores and lesion size by 68.5% and 74%, respectively 42 PRP Significant decrease in lesion size and pain score 38 Oral mucositis Platelet lysate Healing was good-to-complete in 5 out of 7 cases 50 Platelet gel Platelet gel resulted in improvement of oral mucosa, revealing restitutio ad integrum 46 Platelet gel PC resulted in improved quality of life and pa...…”
Section: Clinical Application Of Pc In Chronic Oral Mucosal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“… Lesion Type of PCs Effect of PCs Ref. Oral lichen planus PRF membrane PRF resulted in a decrease in lesions' size within 3 weeks of treatment 36 Platelet solution PC improved quality of life and decreased pain 35 PRP Complete regression of the lesion after 4 weeks 41 PRP 90% of patients reported complete resolution of erythema 40 PRP Significant reduction in pain, size of the lesion and inflammation 37 i-PRF i-PRF reduced the lesion size by 59.8% and reduced the VAS scores by 47.6% 65 i-PRF i-PRF reduced pain and lesion's size 44 PRP PRP reduced pain and size of the ulcers 39 i-PRF i-PRF reduced VAS scores and lesion size by 68.5% and 74%, respectively 42 PRP Significant decrease in lesion size and pain score 38 Oral mucositis Platelet lysate Healing was good-to-complete in 5 out of 7 cases 50 Platelet gel Platelet gel resulted in improvement of oral mucosa, revealing restitutio ad integrum 46 Platelet gel PC resulted in improved quality of life and pa...…”
Section: Clinical Application Of Pc In Chronic Oral Mucosal Diseasesmentioning
confidence: 99%
“… 37 , 38 , 39 , 40 , 41 In addition, a randomized clinical trial showed that PRF injections in OLP resulted in a significant reduction of lesion size, pain score, and decreased mean values of oral health impact profile scale, which were comparable to corticosteroid injections. 42 , 43 , 44 Overall, clinical studies suggest that applying PCs either topically or intralesional for an average of eight weeks would be a valid treatment option for recalcitrant OLP lesions.…”
Section: Clinical Application Of Pc In Chronic Oral Mucosal Diseasesmentioning
confidence: 99%
“…In recent years, scholars have found PRF local injections to be comparable to tretinoin (TA) in relieving OLP pain, suggesting a role in EOLP pain control ( Bennardo et al., 2021 ). However, one study found that TA showed better treatment results on the visual pain analog scale (VAS) and semi-quantitative REU (reticulo-erosion-ulcer) scores when both were injected at the same lesion site ( Al-Hallak et al., 2023 ). Platelet-rich fibrin (i-PRF) and CS for EOLP both reduce pain and lesion size, but i-PRF is less expensive ( Saglam et al., 2021 ).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Studies showed a tendency for lesions to manifest in the fourth and fifth decades. While the studies of Al-Hallak et al [ 21 ] and Bennardo et al [ 22 ] compared i-PRF with triamcinolone acetonide (TA), Saglam et al [ 23 ] compared i-PRF with methylprednisolone acetate (MPA). The Thongprasom score was calculated to assess the surface area of the lesion in studies by Bennardo et al [ 22 ] and Saglam et al [ 23 ].…”
Section: Reviewmentioning
confidence: 99%